2015
DOI: 10.1038/srep16121
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Rhp-PSP, a member of YER057c/YjgF/UK114 protein family with antiviral properties, from the photosynthetic bacterium Rhodopseudomonas palustris strain JSC-3b

Abstract: Rhodopseudomonas palustris strain JSC-3b isolated from a water canal adjacent to a vegetable field produces a protein that was purified by bioactivity-guided fractionation based on ammonium sulfate precipitation, ion-exchange absorption and size exclusion. The protein was further identified as an endoribonuclease L-PSP (Liver-Perchloric acid-soluble protein) by shotgun mass spectrometry analysis and gene identification, and it is member of YER057c/YjgF/UK114 protein family. Herein, this protein is designated R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The TMV U1 strain was propagated and purified from its systemic host Nicotiana tabacum cv. Huangmiaoyu as described by Pin Su (Su et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The TMV U1 strain was propagated and purified from its systemic host Nicotiana tabacum cv. Huangmiaoyu as described by Pin Su (Su et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Another representative of Alphaproteobateria, Rhodopseudomonas palustris, is a photosynthetic purple non-sulfur bacteria (Austin et al, 2015) exhibiting diverse biological activities. Su et al (2015) found an antiviral protein showing significant inhibitory activity against tobacco mosaic virus (TMV) in vivo and in vitro in the JSC-3b bacterial strain. Nookongbuta et al (2020) demonstrated that exopolymeric substances (EPS), lipopeptides and photopigments extracted from the KTSSR54 strain showed antifungal activity against three rice fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that extracellular proteins produced by beneficial microorganisms have antiviral activity. Such extracellular proteins include SAMP from S. marcescens strain S3, 21 protein elicitor PeBL1 from B. laterosporus strain A60, 28 and activator proteins from Rhodopseudomonas palustris strain JSC‐3b 19 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, isolating antiviral molecules from beneficial microorganisms is one of the important strategies to prevent and control virus diseases in plants 19 . For example, a novel polysaccharide composed of D‐mannose, D‐galactose and D‐glucose from the cultured filtrate of fungus Trichosporon confers a much stronger local but not systemic resistance against TMV through priming pathogen‐related defense genes 20 .…”
Section: Introductionmentioning
confidence: 99%